Effect of compaction, delayed sealing and aerobic exposure on forage choice and short‐term intake of maize silage by goats. (20th December 2017) - Brüning, D.; Gerlach, K.; Weiß, K.; Südekum, K.‐H.
Abstract: Forage choice and intake by ruminants depend on various factors. This study aimed to determine the effects of compaction, delayed sealing and aerobic exposure on forage choice and short‐term dry‐matter intake (DMI) of maize silage by goats. Whole‐crop maize (277 g/kg dry matter [DM]) in 120‐L silos was compacted at either low (194 kg DM/m 3 ) or high (234 kg DM/m 3 ) density, and sealed immediately at day 0 or with a delay at day 2 or day 4 post‐filling, making a total of six treatments. After ensiling for at least 175 days, silages were exposed to air for 6 days. In 2‐day intervals, silages were sampled for chemical analyses and were vacuum‐stored for use in preference trials. During the experimental phase, each possible two‐way combination of the aerobically exposed silages (days 0, 2, 4 and 6 post‐opening) of the treatments and lucerne hay was offered as free choice to goats ( n  = 5) for 3 hr. Exposing silages to air for >4 days post‐opening caused strong avoidance and lowest intakes. Under the conditions of the study, aerobic exposure after ensiling had a more pronounced effect on silage preference and short‐time DMI than compaction and delayed sealing. Increasing fibre fractions, a deteriorating microbial status and poor silage sensory properties, probably caused by a combination of different fermentation products, can be considered for decrease in preference.